Bereaved parents involvement in maternity hospital perinatal death review processes: 'Nobody even thought to ask us anything' - Änne Helps; Keelin O'Donoghue; Orla O'Connell; Sara Leitao (Wiley, 2023)
Abstract Introduction The death of a baby is devastating for parents, families and staff involved. Involving bereaved parents in their baby's care and in the maternity hospital perinatal death review can help parents manage their bereavement and plan for the future. In Ireland, bereaved parents generally have not been involved in this review process. The aim of our study was to assess parents' perception of how they may be appropriately involved in the maternity hospital perinatal death review in ways that benefit them and the review process itself. Methods Bereaved parents (n = 20) in Ireland were invited to take part in semistructured interviews. Thematic analysis was carried out on the interview transcripts. Results Four main themes were identified based on the participants' views and opinions on how they experienced the review process and how they feel this process may be improved. The themes reflect the journey of the parents through the different stages of the review process: Throughout process; On leaving the hospital; Interaction with the hospital 'waiting in limbo'; Review itself. Identified subthemes highlighted essential aspects of this process and care provided to parents. For the parents, open, honest communication with staff, as well as having a key hospital contact was essential. Parents wished to provide feedback on their experience and wanted to be included in the review of their baby's death, in a way that was sensitive to their needs and the hospital's schedule. Conclusion A respectful, flexible system that allows bereaved parents' involvement in their baby's perinatal death review and is tailored to their needs is essential. A collaborative process between staff and parents can highlight clinical areas in need of change, enhance lessons learned, improve bereavement services and may prevent future perinatal deaths. Public Contribution Bereaved parents were interviewed for this study.